1993
DOI: 10.1007/bf02592286
|View full text |Cite
|
Sign up to set email alerts
|

The biology of stem cell factor, a new hematopietic growth factor involved in stem cell regulation

Abstract: Recently, a new hematopoietic growth factor, stem cell factor, the ligand for the c-kit-proto-oncogene, has been cloned. The gene for this factor or for its receptor are deleted in two well known series of mice mutants which display pleiotropic stem cell defects. Therefore, this factor supposedly plays an important role in stem cell biology. This paper reviews some of the elegant genetic work which led to the discovery of the factor and of its receptor, the biological effects that this factor exerts in the hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Clinically, increasing evidences have shown the therapeutic potential of G-CSF and SCF in patients with ischemic stroke [8, 18, 43]. SCF has been found to stimulate early pluripotent and committed stem cells to form colony-forming units and act synergistically with other growth factors such as GCSF to increase the production of hematopoietic cells [44, 45]. Previous findings have also reported G-CSF’s ability to reduce lesion volumes and improve neurological outcome at 48 hours after cerebral ischemia in rodents [21, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, increasing evidences have shown the therapeutic potential of G-CSF and SCF in patients with ischemic stroke [8, 18, 43]. SCF has been found to stimulate early pluripotent and committed stem cells to form colony-forming units and act synergistically with other growth factors such as GCSF to increase the production of hematopoietic cells [44, 45]. Previous findings have also reported G-CSF’s ability to reduce lesion volumes and improve neurological outcome at 48 hours after cerebral ischemia in rodents [21, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Granulocyte colony-stimulating factor in combination with SCF was also found to mobilize primitive bone marrow cells in splenectomized mice (5). Stem cell factor stimulates early pluripotent and committed stem cells to form colony-forming units and can act synergistically with other growth factors, such as IL-1, IL-3, IL-6, GM-CSF, G-CSF, and erythropoietin to increase the production of hematopoietic cells (6,7). Several studies have shown that G-CSF improves cardiac function and left ventricular (LV) remodeling after MI (5,8 -10).…”
mentioning
confidence: 97%
“…Since the first discovery of hematopoietic stem cells of mice (69), there have been significant advances in identification, purification, in vitro expansion and genetic manipulation of various stem cells from different tissues (70)(71)(72)(73)(74)(75)(76)(77)(78). Since the first discovery of hematopoietic stem cells of mice (69), there have been significant advances in identification, purification, in vitro expansion and genetic manipulation of various stem cells from different tissues (70)(71)(72)(73)(74)(75)(76)(77)(78).…”
Section: Toward Gene Therapy: Fusion Of Stem Cells With Hacmentioning
confidence: 99%